Millie Fleur's Poison Garden - Mandin, Christy (New York : Orchard Books, an imprint of Scholastic Inc, 2024)
"Millie Fleur La Fae is new in Garden Glen, and she plans to plant her garden of strange and sometimes dangerous plants, but the town garden club does not approve of her and wants to tear it down--
Keywords: Gardens -- Juvenile fiction; Dangerous plants -- Juvenile fiction; Individuality -- Juvenile fiction; Conformity -- Juvenile fiction; Gardens -- Fiction; Dangerous plants -- Fiction; Individuality -- Fiction; Conformity -- Fiction; Picture books